The Effect of Marijuana Legalization on the Trajectories of Hard Drug–Related Hospitalizations: A Growth Curve Analysis of the County-Level State Inpatient Database in Washington, 2009–2015. (July 2020) - Park, Seong-min; Shen, Jay J.; Yoo, Ji Won; Reed, Shon M.
Two antithetical arguments have raised controversies over the effect of recreational marijuana legalization on hard drug use. The gateway perspective posits that marijuana use diffuses hard drug use; however, recent studies argue that marijuana legalization displaces hard drug use. This study examines these conflicting arguments by investigating temporal patterns of hard drug–related hospitalizations (HDHs) before and after marijuana legalization. Using county-level State Inpatient Database data from Washington State for the years 2009–2015, along with other federal data sources, this study assesses temporal changes in HDH using growth curve modeling. Initial findings show support for the displacement perspective, though controlling for other county-level factors (education and economic change) indicates that the legalization of recreational marijuana may be a gateway toward harder drugs. Considering the economic situation of the United States during the study period, this study concludes that marijuana legalization functioned as a gateway toward increased hard drug use.